Mass of Higgs and stability of the vacuum - Chai, Chang Kai (Nanyang Technological University, 2023)
The discovery of Higgs boson in 2012 is one of the great milestones in particle physics and showed another result predicted from Standard Model of elementary particles. However, there are certain problems arisen in this model, including the vacuum stability, which urge physicists to look for possible new physics beyong Standard Model. In this thesis, we first revise the Glashow-Weinberg-Salam model of electroweak theory as well as Higgs mechanism. The idea of how problem of vacuum stability arises is discussed too. To see how Higgs mechanism can work in other model, the minimal B - L model is studied with the gauge bosons’ masses evaluated. Then, we formulate the theory of supersymmetry in detail and eventually attempt to develop a supersymmetric version of electroweak theory. The Higgs potential’s vacuum stability of this model is discussed in the end of the thesis.